Rules of origin and consumer-hurting free trade agreements - Hiroshi Mukunoki; Hirofumi Okoshi (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2019)
This study examines how the rules of origin (RoO) of a free trade agreement (FTA) affect firms' pricing strategies. A value-added criterion (VAC) of the RoO requires firms to add more than a certain level of values within an FTA when firms use inputs originating from outside the FTA. The VAC may have a collusive effect that benefits all firms if it induces an offshoring firm to manipulate its output price. Meanwhile, a consumer-hurting FTA formation is possible even if all firms make tariff-free exports. Furthermore, such an FTA formation may worsen total welfare.
urn:nbn:de:bvb:19-epub-61759-3
Keywords: F13; F15; L11; 330; Rules of origin; Free trade agreement; Pricing strategy